Analysis of marketing strategy at JeKo resaturant - Putra, Ridho Maulana; Nahor, Mian Ivany Banjar; Suastika , I Kadek Dwi; Tinu, Maria Mayasari; Indah, Mawar; Ardhika, Ni Kadek Rhiska Lesthari; Sananta, I Kadek Bagus Pramoedia (YAYASAN MITRA PERSADA NUSANTARA, 2024)
This research aims to find out how marketing strategy is implemented at JeKo. JeKo is classified as a restaurant, but the term